Low power design methodology in quantum-dot cellular automata. (January 2022) - Sadhu, Arindam; Das, Kunal; De, Debashis; Kanjilal, Maitreyi Ray
Abstract: The signal distribution network (SDN) in VLSI (Very Large Scale Integration) technology consumes enormous power and layout area among different components. In this article, an extensive focus has been given to designing low-power interconnection in QCA technology. Revolving door elimination techniques, a new crossover methodology, and a circuit without fixed polarized cells are proposed in this research work to make an energy-efficient QCA circuit. The revolving door elimination technique provides us almost 50% energy efficiency over the standard crossover technique. The proposed signal distribution network (SDN) methodology encountered 47% area and nearly 15% energy benefits concerning previously reported SDN techniques. New methodologies are implemented on different nano-communication and computing circuits like XOR gate, odd-even parity generator, priority encoder, decoder, pseudo-random number generator (PRNG) to verify the functionality of proposed methodologies.